Pengaruh Promosi Kesehatan Tentang Filariasis Terhadap Sikap Masyarakat Dalam Upaya Pencegahan Penyakit Filariasis Di Daerah Pantura Kabupaten Subang - Widy Utami, Novita, Badar Kirwono, SKM, M.Kes, Anisa Catur Wijayanti, SKM., M.Epid (2015)
Filariasis is a disease caused by parasitic nematode infection, the disease is rarely fatal, but it can reduce the productivity of sufferers due to the onset of physical disorders. In Indonesia in 2014 were reported as chronic cases 8003 people scattered in 32 provinces and 497 districts / cities (60.4%) endemic, in West Java reached 480 cases, adapundi Subang district as many as 28 people with elephantiasis acute an already difficult cured. This study aims to determine the effect of health promotion on filariasis against the attitude of society in the prevention of filariasis in the north coast area Subang district. This type of research is quasy experimental research with pre and post test without control (control yourself). Samples were taken by using cluster sampling technique and obtained 220 respondents. Data were analyzed using SPSS by using a different test that is Wilcoxon test with a significance level of 95%. The results showed that no significant effect on the provision of health promotion filariasis against the attitude of the community in the prevention of filariasis in Subang district Pantura area (p = 0.000) and the average value of the attitude before being given health promotion at 54.92 and after a given health promotion amounting to 58.18.